Cell Proliferation and Collective Cell Migration During Zebrafish Lateral Line System Development Are Regulated by Ncam/Fgf-Receptor Interactions - Dries, Ramona; Lange, Annemarie; Heiny, Sebastian; Berghaus, Katja I.; Bastmeyer, Martin; Bentrop, Joachim (Frontiers in Cell and Developmental Biology, 2021)
The posterior lateral line system (pLLS) of aquatic animals comprises small clustered mechanosensory organs along the side of the animal. They develop from proneuromasts, which are deposited from a migratory primordium on its way to the tip of the tail. We here show, that the Neural Cell Adhesion Molecule Ncam1b is an integral part of the pathways initiating and regulating the development of the pLLS in zebrafish. We find that morpholino-knockdowns of ncam1b (i) reduce cell proliferation within the primordium, (ii) reduce the expression of Fgf target gene erm, (iii) severely affect proneuromast formation, and (iv) affect primordium migration. Ncam1b directly interacts with Fgf receptor Fgfr1a, and a knockdown of fgfr1a causes similar phenotypic changes as observed in ncam1b-morphants. We conclude that Ncam1b is involved in activating proliferation by triggering the expression of erm. In addition, we demonstrate that Ncam1b is required for the expression of chemokine receptor Cxcr7b, which is crucial for directed primordial migration. Finally, we show that the knockdown of ncam1b destabilizes proneuromasts, suggesting a further function of Ncam1b in strengthening the cohesion of proneuromast cells.